Issues of Ecological Education - Adhamovich, Ergashev Ulugbek (Central Asian Journal of Literature, Philosophy and Culture, 2022)
The article focuses on the ethical aspects of the response to environmental problems, and offers a number of ethical approaches to the modern problems of raising environmental culture in a person.